1990
DOI: 10.1093/infdis/162.2.313
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Behavior of Genetically Engineered Herpes Simplex Viruses R7017 and R7020. II. Studies in Immunocompetent and Immunosuppressed Owl Monkeys (Aotus trivirgatus)

Abstract: The genetically engineered herpes simplex virus strains R7017 and R7020 were tested in owl monkeys (Aotus trivirgatus) previously shown to model herpetic diseases of immunocompromised patients and neonates. In contrast to the lethal disease seen in monkeys receiving 100-1,000 plaque-forming units (pfu) of wild-type virus, inoculation of greater than or equal to 10(6) pfu of recombinant viruses produced local lesions and viral shedding but not disseminated disease. Latent recombinant viruses were recovered from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
81
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(82 citation statements)
references
References 10 publications
0
81
0
Order By: Relevance
“…Determined by the onset of severe symptoms, the survival time in our study is, however, comparable to the 6-8 days reported by Melendez et al 10 as well as to the 6-19 days reported by Meingier et al after intradermal or vaginal infection at titers of wildtype HSV-1 and HSV-2 as low as 10 2 -10 3 PFU. 12,13 The common marmosets succumbed much sooner than the owl monkey, showing severe symptoms usually around 6 days post-injection, and their brains also displayed marked infection with HSV, with far more extensive HSV immunopositivity than seen in the owl monkeys. This survival time corresponds with the findings of Cho et al, 4 who reported an average survival time of 8 days after injecting 10 5 PFU HSV-1 intracerebrally into two marmosets.…”
Section: Discussionmentioning
confidence: 99%
“…Determined by the onset of severe symptoms, the survival time in our study is, however, comparable to the 6-8 days reported by Melendez et al 10 as well as to the 6-19 days reported by Meingier et al after intradermal or vaginal infection at titers of wildtype HSV-1 and HSV-2 as low as 10 2 -10 3 PFU. 12,13 The common marmosets succumbed much sooner than the owl monkey, showing severe symptoms usually around 6 days post-injection, and their brains also displayed marked infection with HSV, with far more extensive HSV immunopositivity than seen in the owl monkeys. This survival time corresponds with the findings of Cho et al, 4 who reported an average survival time of 8 days after injecting 10 5 PFU HSV-1 intracerebrally into two marmosets.…”
Section: Discussionmentioning
confidence: 99%
“…These viruses were derived from NV1020, a nonselected clonal derivative of R7020 obtained from B Roizman. 36,37 NV1021 and NV1022 are precursors of NV1023 and NV1042 and derived from NV1020. NV1021 contains the E. coli lacZ gene under control of the ICP47 (US12) promoter.…”
Section: Virusesmentioning
confidence: 99%
“…[8][9][10][11] The first attenuated HSV virus to be constructed and analyzed as a viral vaccine in humans was the NV1020 (formerly R7020) strain. 12,13 This virus, based on HSV-1 strain F, has a portion of the unique short region of the viral genome encoding glycoproteins G, D, I and E, replaced by the homologous region from HSV-2, and possesses one copy of ICP4. This virus was very strongly attenuated in rodents and primates.…”
Section: Live Viral Anti-hsv Vaccinementioning
confidence: 99%
“…41 In many of these studies, the efficacy of G207 has been compared with that of the above mentioned NV1020, which was shown to be too attenuated to work as a live viral vaccine. 12,13 Moreover, NV1020 is currently being investigated in Phase I clinical trials for patients with colon cancer that has metastasized to the liver and has proven recalcitrant to chemotherapy. This is also the first trial to investigate administration via intravascular delivery.…”
Section: Oncolytic Hsv Attenuated Virusesmentioning
confidence: 99%
See 1 more Smart Citation